PENERAPAN RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA PT. GELORA PERKASA - Sintaria Sibarani; Ratna Dina Marviana (UNIVERSITAS DHARMAWANGSA, 2021)
Financial performance is a success achieved by a company which shows thefinancial condition of company in a certain periods. In assessing the financialperformance, financial ratio is one of analytic tools that can be used, which can bedone by comparing annual financial data on financial statement post. The resultwill show the achievement achieved by a company. This research aim to determinethe financial performance of PT. Gelora Perkasa in terms of liquidity, solvability,and probability ratios. The method uses in this research is descriptive method.Population of this research is the company financial report in 2016-2019. Thesample of this research is statement of financial position and income statementduring 2016-2019 period. Based on the results of data processing, the financialperformance of PT. Gelora Perkasa for current ratio, cash ratio, debt to asset ratio,debt to equity ratio, return on investment and return on equity ratio consecutively1,58 times, 0,30 times, 60,01%, 129,76%, 2,60%, and 4,77%. Based on the resultsof processing data, it is known that the financial performance of PT. GeloraPerkasa in terms of liquidity ratio which interpreted by current and cash ratio,solvability ratio which interpreted by debt to asset and debt to equality ratio,profitability ratio which interpreted by return on investment and return on equityare all not in a good condition.